Nanomaterials for Drug Delivery and Cancer Therapy - Nicoletta, Fiore P.; Iemma, Francesca (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint of "Nanomaterials for Drug Delivery and Cancer Therapy" covers the recent advances in the use of nanoparticle systems, with an emphasis on preparation and characterization methods, functionalization chemistry, and their associated applications in drug delivery and cancer therapy.